Homogenization studies for optical sensors based on sculptured thin films - Jamaian, Siti Suhana (2012)
In this thesis we investigate theoretically various types of sculptured thin film (STF) envisioned as platforms for optical sensing. A STF consists of an array of parallel nanowires which can be grown on a substrate using vapour deposition techniques. Typically, each nanowire has a diameter in the range from » 10¡300 nmwhile the film thickness is .1¹m. Through careful control of the fabrication process, both the optical properties and the porosity of the STF can be tailored to order. These abilities make STFs promising for optical sensing applications, wherein it is envisaged that the material to be sensed infiltrates the void region in between the parallel nanowires and hence changes the optical properties of the STF. Various homogenization formalisms can be used to estimate the constitutive parameters of the infiltrated STFs. In this thesis two different homogenization formalisms were used: the Bruggeman formalism (extended and non–extended versions) and the strong-permittivityfluctuation theory (SPFT). These were used in investigations of the following optical–sensing scenarios: (i) Electromagnetic radiation emitted by a dipole source inside an infiltrated chiral STF. The effects of using the extended Bruggeman homogenization formalism, which takes into account the nonzero size of the component particles,were studied. (ii) Surface–plasmon– polariton waves on ametal–coated, infiltrated columnar thin film. The influences of using the extended SPFT formalism, which takes into account the nonzero size of the component particles and their statistical distributions, were explored. (iii) A metal-coated infiltrated chiral STF which supports both surface-plasmon-polariton waves and the circular Bragg phenomenon. The possibility of using in parallel both surface-plasmon-polariton waves and the circular Bragg phenomenon was investigated using the non–extended Bruggeman formalism. Our numerical studies revealed that the design performance parameters of the infiltrated STF are bode well for these optical–sensing scenarios. The use of inverse Bruggeman formalism was also investigated: this was found to be problematic in certain constitutive parameter regimes, but not those for optical–sensing scenarios considered in this thesis.